TikTok as an ‘angel’ or ‘demon’ learning tool in sport sciences education: A narrative critical review - Samuel López-Carril; Nicholas M. Watanabe; Christos Anagnostopoulos (Social Sciences and Humanities Open)
This study explored the integration of TikTok, an emerging social media platform, into sport sciences education. Despite its popularity among youth, TikTok's educational impact has been understudied. Through a narrative critical rereview, this work analyzes sport sciences education literature to uncover TikTok's dual nature as both beneficial (‘angel’) and potentially harmful (‘demon’). Emphasizing the need for risk assessment before educational integration, this study identifies TikTok's unexplored potential and challenges. Six studies were identified during the review, demonstrating that the benefits of using TikTok in sport sciences outweigh the risks. Therefore, the use of TikTok in sport sciences is recommended, and faculty and researchers are encouraged to explore this emerging topic further. The article concludes with a proposed research agenda that serves as a starting point for future investigations into the impact and implications of TikTok use in higher education. The results of this study may interest educators and educational policymakers in integrating TikTok into higher education.